One-pot hydrothermal synthesis of nano-sheet assembled NiO/ZnO microspheres for efficient sulfur dioxide detection. Issue 6 (15th April 2020) - Si, Wenxu; Du, Wenjing; Wang, Fenglong; Wu, Lili; Liu, Jiurong; Liu, Wei; Cui, Ping; Zhang, Xiaomei
Abstract: The nano-sheet assembled NiO/ZnO microspheres with a diameter of ca. 2 μm have been synthesized via facile hydrothermal method followed by a thermal treatment process. The gas-sensing measurement results show that the sensor using nano-sheet assembled NiO/ZnO microspheres exhibits improved response to sulfur dioxide gas compared with the pure ZnO microspheres sensor. In particular, the sensor with a Ni/Zn molar ratio of 0.5 (0.5 mol% NiO/ZnO) shows high response value (S = 107) and superior selectivity to 10 ppm sulfur dioxide at a low operating temperature of 160 °C and the detection limit of the NiO/ZnO sensor toward sulfur dioxide is down to 1 ppm (S = 6). The enhanced sensing performance is attributed to the formation of p-n heterojunctions on the interface, the catalytic function of NiO and the three-dimensional microspheres composed of the lamellar structure with a large specific surface area. The three-dimensional microspheres provide more active sites for gas adsorption, and the interlayer gap facilitates the diffusion of gas in three-dimensional structure, resulting in high sensitivity and superior selectivity. This work provides a simple method for the synthesis of NiO/ZnO heterojunction microspheres with superior gas-sensing performance, which can be used as a potential material for sulfur dioxide detection.